Predominance of Heart Failure With Preserved Ejection Fraction in Postmenopausal Women: Intra- and Extra-Cardiomyocyte Maladaptive Alterations Scaffolded by Estrogen Deficiency - Adekunle, Adebayo Oluwafemi; Adzika, Gabriel Komla; Mprah, Richard; Ndzie Noah, Marie Louise; Adu-Amankwaah, Joseph; Rizvi, Ruqayya; Akhter, Nazma; Sun, Hong (Frontiers in Cell and Developmental Biology, 2021)
Abstract Heart failure (HF) remains a public health concern as it is associated with high morbidity and death rates. In particular, heart failure with preserved ejection fraction (HFpEF) represents the dominant (>50%) form of HF and mostly occurring among postmenopausal women. Hence, the initiation and progression of the left ventricular diastolic dysfunctions (LVDD) (a typically clinical manifestation of HFpEF) in postmenopausal women have been attributed to estrogen deficiency and the loss of its residue cardioprotective effects. In this review, from a pathophysiological and immunological standpoint, we discuss the probable multiple pathomechanisms resulting in HFpEF, which are facilitated by estrogen deficiency. The initial discussions recap estrogen and estrogen receptors (ERs) and β-adrenergic receptors (βARs) signaling under physiological/pathological states to facilitate cardiac function/dysfunction, respectively. By reconciling these prior discussions, attempts were made to explain how the loss of estrogen facilitates the disruptions both ERs and βARs-mediated signaling responsible for; the modulation of intra-cardiomyocyte calcium homeostasis, maintenance of cardiomyocyte cytoskeletal and extracellular matrix, the adaptive regulation of coronary microvascular endothelial functions and myocardial inflammatory responses. By scaffolding the disruption of these crucial intra- and extra-cardiomyocyte physiological functions, estrogen deficiency has been demonstrated to cause LVDD and increase the incidence of HFpEF in postmenopausal women. Finally, updates on the advancements in treatment interventions for the prevention of HFpEF were highlighted.